HIPERBOLA DAN SIMILE DALAM NOVEL MUKENAH & SAJADAH UNTUK SOYA KARYA MARIA BO NIOK: KAJIAN STILISTIKA - Sutopo, Bakti (SASINDO, 2014)
This discussion aims to describe the hyperbole and the simile in the novelMukenah and Sajadah untruk Soya Maria Bo Niok work. The discussion was necessarybecause of the literary works, including novels, as the discourse of language that canbe assessed in terms of linguistics, especially with a bunch of disciplined Stilistika. Inaddition, the novel Mukenah & rug for Soya has a distinctive style, especially the use ofhyperbole figure of speech and similes in canoes as means of aesthetic and rhetorical.Working method is the method of literature research work by collecting dataobjects such as text, which is novel Mukenah & rug for Soya Maria Bo Niok works wellas a material object, and use Stilistika as a theoretical basis. Stilistka is interdisciplinarybetween linguistics to literary studies. In addition, Stilistika examine aspects oflanguage use distinctive and unique in the literature, among which figure of speech /figurative language. To obtain the answer, there are two problems in the formulationof this discussion, namely the use of hyperbole and simile as well as the function andpurpose of their use in novel Mukenah & rug for Soya works of Maria Bo Niok.Keywords: stilistika, literature, language, style, and a figure of speech